Persuasive Ethical Strategies in Gubernatorial Campaign Speeches : A Comparative Study - Dinda Rahmayani; Nazalia Rahma; Rita Hartati (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study examines the rhetorical strategies employed by gubernatorial candidates Edy Rahmayadi and Bobby Nasution during the 2024 North Sumatra election, focusing on their use of ethos, pathos, and logos within Aristotle’s rhetorical framework. The research also compares their rhetorical approaches and evaluates their alignment with ethical communication principles, including transparency, truthfulness, and accountability. Using a qualitative approach, this study analyzes five campaign speeches from each candidate to identify persuasive strategies, compare their communication styles, and assess their ethical implications. Findings reveal that while both candidates effectively employ rhetorical strategies, their approaches differ significantly. Edy Rahmayadi emphasizes his track record and regional pride, often adopting a defensive tone to address criticisms. Bobby Nasution presents a more inclusive, proactive, and solution-oriented rhetorical style, appealing to optimism and collaboration. Furthermore, Bobby’s speeches align more closely with ethical communication principles through transparent, truthful, and actionable commitments, whereas Edy demonstrates partial alignment, occasionally deflecting responsibility or lacking specificity in his arguments. This research contributes to understanding political rhetoric and its ethical dimensions, offering insights into the interplay between persuasion and ethical leadership in electoral campaigns.